Evaluasi Kinerja & Analisa Sistem Informasi Akademik menggunakan model Task Technology Fit - Dessyana Kardha (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
The system development process should ideally begin with proper analysis and design so that the system can still be developed easily even though there are deficiencies in system functions during the implementation process. In this study, we develop a system design that balances task requirements, individual capabilities, and technological functions to minimize system deficiency gaps, with the aim that when evaluated, the system will be a quality product that meets user needs. To minimize the gap between the function and the completion of the task, an evaluation is carried out using the Task Technology Fit (TTF) model developed by Goodhue and Thompson (1995). The case study in this research is STMIK AUB Surakarta. The feedback provided is in the form of a system design that has been adjusted to the needs of business processes in the form of a flowchart and compiled based on the results of an analysis using the Task Technology Fit model.